KEBIJAKAN HUKUMAN MATI DAN PROBLEMATIKA PENERAPAN DITINJAU DARI HAK ASASI MANUSIA - Abshar, Rijal Ulil (Universitas Borneo Tarakan, 2023)
AbstractIndonesia is one of the countries that still maintains and acknowledges thelegality of the death penalty as one of the ways to punish perpetrators of criminalacts. Furthermore, the existence of the death penalty in Indonesia will continueto persist in the future, as it is retained as one of the criminal sanctions in thenew draft of the Criminal Code. The death penalty, in addition to being the mostsevere punishment, is also a highly daunting penalty, particularly for convictsawaiting execution. This research employs a normative juridical approach, amethod in which law is conceptualized as norms, rules, principles, or doctrines.The approach in this study utilizes secondary data comprising primary legalmaterials, secondary legal materials, and tertiary legal materials. Based on thefindings of this research, the policy of the death penalty, when viewed throughthe lens of Human Rights, significantly contradicts Human Rights principles as itpertains to the fundamental right to life. The 1945 Constitution of Indonesia, asthe written fundamental law of the nation, has declared that every individual hasthe right to life and the protection of that life.Keywords: the death penalty, death penalty policy, human rights